Vagally-mediated heart block after myocardial infarction associated with plasticity of epicardial neurons controlling the atrioventricular node - Tompkins, John D.; Buckley, Una; Salavatian, Siamak; Shivkumar, Kalyanam; Ardell, Jeffrey L. (Frontiers in Synaptic Neuroscience, 2022)
Imbalances in the opposing actions of sympathetic and parasympathetic nerves controlling the heart enhance risk for arrhythmia and sudden cardiac death after myocardial infarction (MI). Plasticity in peripheral neuron function may underlie the observed changes in cardiomotor nerve activity. We studied vagal control of the heart in pigs after chronic infarction of the left ventricle. Stimulation of the cervical vagus nerve produced greater bradycardic responses 8-weeks after MI. Recordings of epicardial electrocardiograms demonstrate increased severity and duration of atrioventricular (AV) block in MI-pigs during 20 Hz vagal stimulation. Intracellular voltage recordings from isolated neurons of the inferior vena cava-inferior left atrium (IVC-ILA) ganglionated plexus, a cluster of epicardial neurons receiving innervation from the vagus known to regulate the AV node, were used to assess plasticity of membrane and synaptic physiology of intrinsic cardiac neurons (ICNs) after MI. Changes to both passive and active membrane properties were observed, including more negative resting membrane potentials and greater input resistances in MI-pig ICNs, concomitant with a depression of neuronal excitability. Immunoreactivity to pituitary adenylate cyclase-activating polypeptide (PACAP), a cardiotropic peptide known to modulate cardiac neuron excitability, was localized to perineuronal varicosities surrounding pig IVC-ILA neurons. Exogenous application of PACAP increased excitability of control but not MI-ICNs. Stimulation (20 Hz) of interganglionic nerves in the ex vivo whole-mount preparations elicited slow excitatory postsynaptic potentials (sEPSPs) which persisted in hexamethonium (500 μM), but were blocked by atropine (1 μM), indicating muscarinic receptor-mediated inhibition of M-current. Extracellular application of 1 mM BaCl2 to inhibit M-current increased neuronal excitability. The muscarine-sensitive sEPSPs were observed more frequently and were of larger amplitude in IVC-ILA neurons from MI animals. In conclusion, we suggest the increased probability of muscarinic sEPSPs play a role in the potentiation of the vagus nerve mediated-slowing of AV nodal conduction following chronic MI. We identify both a novel role of a muscarinic sensitive current in the regulation of synaptic strength at ICNs projecting to the AV node, and demonstrate changes to both intrinsic plasticity and synaptic plasticity of IVC-ILA neurons which may contribute to greater risk for heart block and sudden cardiac death after MI.